2015
DOI: 10.1007/s11695-015-1811-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleeve Gastrectomy Plus Side-to-Side Jejunoileal Anastomosis for Type 2 Diabetes Control in an Obese Rat Model

Abstract: JI-SG induced higher ghrelin and GLP-1 levels and improved glycemic control in Zucker diabetic fatty rats. Compared with SG and RYGB, JI-SG appeared to be a simple, relatively safe, and more effective procedure for treating type 2 diabetes and obesity in this animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…The db/db mouse has a dysfunctional leptin receptor that leads to obesity and insulin resistance. SG does not lead to sustained weight loss in mice deficient in leptin signaling (11)(12)(13)(14)(15), but we observed improved glycemic control even after mice had surpassed their presurgical weight and when compared with pair-fed mice. The improvement was reflected mainly in increased peripheral hepatic insulin sensitivity and not in b-cell recovery and was characterized by hepatic regulation of peroxisome proliferator-activated receptor-a (PPARa) and hepatocyte nuclear factor-a (HNF4a) target genes.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…The db/db mouse has a dysfunctional leptin receptor that leads to obesity and insulin resistance. SG does not lead to sustained weight loss in mice deficient in leptin signaling (11)(12)(13)(14)(15), but we observed improved glycemic control even after mice had surpassed their presurgical weight and when compared with pair-fed mice. The improvement was reflected mainly in increased peripheral hepatic insulin sensitivity and not in b-cell recovery and was characterized by hepatic regulation of peroxisome proliferator-activated receptor-a (PPARa) and hepatocyte nuclear factor-a (HNF4a) target genes.…”
contrasting
confidence: 53%
“…Studies comparing nonobese patients and murine models who had lost weight after bariatric surgery or food restriction have identified weight-independent effects of surgery (10,(31)(32)(33). Rodents deficient in leptin signaling are hyperphagic and have been shown by us and others to gain weight after surgery, highlighting the importance of leptin in weight loss after SG (11)(12)(13)(14)(15)(34)(35)(36). Moreover, these models decouple surgical effects from weight loss while keeping experimental groups obese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis including 16 RCT with a total of 1,132 patients revealed that the RYGB procedure was more effective than SG in terms of weight loss and short-term glycemic control in patients with and without T2D [21]. Wang et al [22] compared the effects of the RYGB and SG procedures in ZDF rats and found that the RYGB group had a greater weight loss than the SG group every week and better glucose control 5 weeks after the operation. Our observational findings in animal models further support the previous conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…To improve LSG's success, an additional intestinal bypass surgery combined with traditional SG (Sleeve Gasrectomy) side to side with jejunoileal anastomosis (JI-SG) has recently been examined and revealed favorable results in weight loss and enhancement of T2DM remission rate [23,24]. These two combined surgeries (JI-SG) comprise two physiological changes: the first is the exclusion of the gastric body and fundus of the stomach, which declines stomach capacity [25], and the second is side-to-side anastomosis of the ileum and jejunum, which transfers food more rapidly into the terminal ileum, without excluding or resecting any segments of the digestive tract. Based on the hindgut theory, this process of accelerating nutrient delivery to the hindgut produces better glycemic control [26].…”
Section: Different Types Of Surgeriesmentioning
confidence: 99%